Subjective Cognitive Complaints in Cognitively Healthy Older Adults and Their Relationship to Cognitive Performance and Depressive Symptoms - Markova, Hana; Andel, Ross; Stepankova, Hana; Kopecek, Miloslav; Nikolai, Tomas; Hort, Jakub; Thomas-Antérion, Catherine; Vyhnalek, Martin (Journal of Alzheimer's disease, 2017)
BACKGROUND: Subjective cognitive complaints (SCCs) may be an early marker of prodromal Alzheimer's disease. OBJECTIVES: Using a 10-item yes/no SCCs questionnaire (Le Questionnaire de Plainte Cognitive [QPC]), we evaluated the prevalence and distribution of SCCs in cognitively healthy Czech older adults and examined total score and specific QPC items in relation to depressive symptomology and cognitive performance. METHODS: A sample of 340 cognitively healthy older community-dwelling volunteers aged 60 or older from the third wave of the longitudinal project National Normative Study of Cognitive Determinants of Healthy Aging, who underwent a comprehensive neuropsychological assessment and completed the QPC and the 15-item Geriatric Depression Scale (GDS-15). Regression analysis was controlled for age when GDS-15 was the outcome and for age and GDS-15 with cognitive domains as the outcome. RESULTS: 71% reported 1 + SCCs, with prevalence of individual complaints ranging from 4% to 40%. The number of SCCs was associated with GDS-15 (p < 0.001). Personality change (p < 0.001) and Limitation in daily activities (p = 0.002) were significantly associated with higher GDS-15 score and Spatial orientation difficulties (p = 0.019) and Impression of worse memory in comparison to peers (p = 0.012) were significantly associated with lower memory performance. CONCLUSIONS: We identified some cognitive complaints that were very common in our sample. Overall, a higher number of SCCs in well cognitively functioning individuals was most closely related to depressive symptomatology, while some specific complaints reflected lower memory performance and should be considered when screening for people at risk of cognitive decline.
Keywords: Mental Status Schedule; Male; Aging; kognitivní poruchy; longitudinální studie; samostatný způsob života; Aged; mužské pohlaví; senioři; deprese; průzkumy a dotazníky; subjective cognitive complaints; Independent Living; Neuropsychological Tests; Personality; senioři nad 80 let; lidé; ženské pohlaví; osobnost; Humans; záznam o duševním stavu; Cognition Disorders; cognitive functioning; stárnutí; Aged, 80 and over; Longitudinal Studies; neuropsychologické testy; depressive symptoms; prodromal Alzheimer’s disease; Female; Surveys and Questionnaires; Depression; lidé středního věku; Middle Aged